Natural compounds in the fight against Staphylococcus aureus biofilms: a review of antibiofilm strategies - Kashi, Milad; Noei, Milad; Chegini, Zahra; Shariati, Aref (Frontiers in Pharmacology, 2024)
Staphylococcus aureus is an important pathogen due to its ability to form strong biofilms and antibiotic resistance. Biofilms play an important role in bacterial survival against the host immune system and antibiotics. Natural compounds (NCs) have diverse bioactive properties with a low probability of resistance, making them promising candidates for biofilm control. NC such as curcumin, cinnamaldehyde, carvacrol, eugenol, thymol, citral, linalool, coumarin, 1,8-cineole, pinene, cymene, terpineol, quercetin, and limonene have been widely utilized for the inhibition and destruction of S. aureus biofilms. NCs influence biofilm formation through several procedures. Some of the antibiofilm mechanisms of NCs are direct bactericidal effect, disrupting the quorum sensing system, preventing bacteria from aggregation and attachment to surfaces, reducing the microbial surface components recognizing adhesive matrix molecules (MSCRAMMs), interfering with sortase A enzyme, and altering the expression of biofilm-associated genes such as icaADBC, agr, and sarA. Furthermore, these compounds affect extracellular polymeric substances (EPS) and their components, such as polysaccharide intercellular adhesin (PIA) and eDNA. However, some disadvantages, such as low water solubility and bioavailability, limit their clinical usage. Therefore, scientists have considered using nanotechnology and drug platforms to improve NC's efficacy. Some NC, such as thymol and curcumin, can also enhance photodynamic therapy against S. aurous biofilm community. This article evaluates the anti-biofilm potential of NC, their mechanisms of action against S. aureus biofilms, and various aspects of their application.